Corporate Social Responsibility: Activities in and around Visakhapatnam City - Manohar, Y. (DESIDOC Journal of Library & Information Technology, 2013)
The paper discusses the scope and principles of corporate social responsibility and its relevanceto the present day business. It also explains the importance of private fi rms and public sector units ofGovernment of India and their role in extending a helping hand in the overall development of the society.The paper also discusses the role of public libraries in augmenting the welfare schemes of the workingcommunities and bridging the ‘digital divide’ among the various sections of the society. The author describesvarious initiatives undertaken by the public sector undertakings in and around Visakhapatnam. http://dx.doi.org/10.14429/djlit.33.1.3722